Antiretroviral Therapy in HIV-Infected Children With Tuberculosis: A Systematic Review. Issue 5 (May 2018) - Sulis, Giorgia; Amadasi, Silvia; Odone, Anna; Penazzato, Martina; Matteelli, Alberto
Abstract : Background: Tuberculosis (TB) is the major cause of mortality in HIV-infected children globally. Current guidelines about the management of antiretroviral therapy in children with TB are based on a limited number of nonrandomized studies involving small numbers of participants. The aim of the study was to systematically retrieve and critically appraise available evidence on the efficacy and safety of different antiretroviral regimens in children with HIV infection who are receiving treatment for active TB. Methods: We conducted a systematic review of the literature according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Records were retrieved through March 2016 from Medline, Embase and manual screening of key conference proceedings. Four specific research questions assessing available treatment options were defined. Results: Although 4 independent searches were conducted (1 for each Population, Intervention, Comparator, Outcomes question), results were elaborated and interpreted together because of significant overlap among the retrieved records. Six observational studies were selected for qualitative synthesis while meta-analysis could not be performed. Conclusion: Evidence for optimal treatment options for HIV/TB coinfected children is limited. As the global community strives to reach the fast-track HIV treatment targets and eliminate childhood TB deaths, it must ensure that coinfected children are included in key treatment studies and expand this neglected but crucial area of research. Abstract : Supplemental Digital Content is available in the text.